Wizard of most wicked ways - Holmberg, Charlie N., 1988- (Holmberg, Charlie N., 1988- Whimbrel House, 2025)
"Whimbrel House is changing. Merritt and Hulda are raising a family. Owein has signed a marriage contract with the magically compatible Lady Cora, a heavyweight of British nobility who's an ocean away. And the lovely shape-shifting druid Fallon makes a distractingly fetching friend for Owein. But another change is in the air, and this time it's something wicked. The greatest wizard of the millennium, Silas Hogwood, is back--after five years dead. New body, same foul scent, and driven by madness and revenge. Owein, fearing he isn't strong enough to fend off Silas, seeks Cora's help and influence in England. Alarms ringing, Queen Victoria dispatches her League of Magicians, including her personal necromancer, to aid in Owein's defense. As magic, both good and evil, converges on Blaugdone Island, Owein realizes how harrowing the forces against them are. Combating them will require some digging--literally--for half-formed secrets of magic Hulda doesn't want him to have. But no promise, lock, or government red tape will keep Owein from doing what's necessary to protect those he loves. One way or another, Silas will only take Whimbrel House over Owein's third dead body."--Page [4] of Cover.